The Management of Facilities and Infrastructure Based on Management Information System Applications for Goods Owned by State (SIMAK-BMN) - Rumiari Rumiari; Wahyudi Wahyudi; Muhammad Chiar (STKIP Singkawang, 2019)
Abstract. The management weakness of facilities and infrastructure in implementing the application of the State Property Management Information System (SIMAK BMN) is the cause of lack of optimal management of facilities or infrastructure or the application of SIMAK BMN by the school principal in empowering education staff and stakeholders within the madrasa. The purpose of this study was to describe the management of application-based infrastructure and State-Owned Management Information System (SIMAK BMN). The approach used in this study was qualitative research with a type of case study research. The stages in this study consisted of field, field and data processing. Data analysis takes place together with the process of collecting data, reducing data, presenting data, and drawing conclusions/verification. The results obtained in this study were (1) Planning of facilities and infrastructure made by madrasas provides an overview of the planning of needs achieved in the purpose of education; (2) Organizing application-based facilities and infrastructure SIMAK BMN in MTsN 1 Singkawang shoed a positive tendency to implement mechanisms, tasks and organizing functions that are conveyed to all teachers; (3) The implementation of SIMAK BMN application-based facilities and infrastructure at MTsN 1 Singkawang showed a tendency to be less than optimal; (4) Monitoring of application-based facilities and infrastructure SIMAK BMN at MTsN 1 Singkawang showed the tendency to carry out internal reconciliation, external reconciliation and pertangungjawban through semester reports. Therefore, it can be concluded, the management of facilities and infrastructure based on the application of the State Owned Management Information System (SIMAK BMN) at MTsN 1 Singkawang was an attempt to curb the recording of application-based infrastructure through the management of Property Management Information System functions. Country (SIMAK BMN).